Expanding the use of flow diverters beyond their initial indication: treatment of small unruptured aneurysms. (10th May 2017) - Pumar, J M; Mosqueira, A; Cuellar, H; Dieguez, B; Guimaraens, L; Masso, J; Miralbes, S; Blanco-Ulla, M; Souto-Bayarri, M; Vazquez-Herrero, F
Abstract : Background: Experience with the endovascular treatment of unruptured small intracranial aneurysms by flow diverter devices is still limited. Objective: To assess the safety and efficacy of the SILK flow diverter (SFD) in the treatment of small unruptured cerebral aneurysms (<10 mm). Methods: We performed a retrospective review of a prospectively maintained database of patients treated with a SFD between July 2008 and December 2013 at 4 institutions in Spain to identify all patients with small unruptured aneurysms (<10 mm). Data for patient demographics, aneurysm characteristics, and technical procedures were analyzed. Angiographic and clinical findings were recorded during the procedure and at 6- and 12-month follow-ups. Results: A total of 109 small aneurysms were treated with a SFD in 104 patients (78 women; 26 men; mean, median, and range of age: 55.2, 57.1, and 19–80 years, respectively). A total of 60 patients were asymptomatic (57.7%). All except 7 aneurysms (6.4%) arose from the anterior circulation. The mean size of the aneurysms was 4.7±1.9 mm. At 6 months, the neuromorbidity and neuromortality rates were 2.9% and 0.9%, respectively. Imaging at the 12-month follow-up showed complete occlusion, neck remnants, and residual aneurysm in 88.5% (69/78), 7.7% (6/78), and 3.3% (3/78) of cases, respectively. No delayed hemorrhage occurred. Conclusions: The findings suggest that the indications for SFD can be safely extended to small intracranial aneurysms.